Flowable bulk-fill versus layering restorative material on Class II restorations: A randomized clinical trial - Torres, Carlos Rocha Gomes [UNESP]; Mailart, Mariane Cintra [UNESP]; Moecke, Sabrina Elise [UNESP]; Matuda, Amanda Guedes Nogueira [UNESP]; Veloso, Sheyla Mamede [UNESP]; da Silva Ávila, Daniele Mara [UNESP]; Nicoló, Rebeca Di [UNESP]; Borges, Alessandra Bühler [UNESP] (Elsevier, 2024)
Objective: This study evaluated the clinical performance of Class II restorations made with flowable bulk-fill base versus conventional layering ORMOCER-based restorative material in a split-mouth randomized clinical trial. Methods: Thirty patients received two class II restorations (n = 60) performed with different strategies. All preparations received the application of the universal self-etching adhesive system according to the manufacturer's recommendation, followed by the placement of a sectional matrix, wooden wedge, and separation ring. The first restoration was performed using 4 mm of flowable bulk-fill material covered by 2 mm of conventional viscosity restorative material (Bulk-fill technique). The second restoration was performed only with the conventional viscosity material, with a maximum of 2 mm thick increments, up to fill the cavity (Layering technique). After occlusal adjustment, the same polishing system was used for all restorations. Evaluations using the FDI criteria were conducted after 7 days, 12, and 24 months. Data were analyzed with the Fisher's Exact test (α=0.05). Results: From 30 participants, 24 attended the 24-month recall, and 48 restorations were evaluated. All restorations received acceptable overall scores for esthetic and biological properties after this period, while only 6.66 % of the restorations exhibited unacceptable overall scores for the functional properties in both groups. No significant differences between the tested restorative materials and techniques were found for each FDI criterion assessed. The success rate after 2 years was 93.33 % for both groups. Conclusion: Both restorative materials exhibited good clinical performance for the parameters analyzed with no differences between them after 24-month follow-up. Clinical relevance: Flowable bulk-fill ORMOCER-based material is a suitable alternative for direct Class II restorations, providing good clinical outcomes and simplifying the restorative procedure. Clinical trial registration number: RBR-6mvp9w
Keywords: Bulk-fill; Flowable; Layering; Ormocer; Resin composite